Keanekaragaman Makrofauna Tanah pada Lahan Polikultur di Desa Pulau Semambu Kecamatan Indralaya Utara - Lena Weni; A. Madjid (Seminar Nasional Lahan Suboptimal, 2020)
Weni L,  Madjid A.  2020. Diversity of soil macrofauna on polyculture land in pulau semambu village north Indralaya district. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Soil macrofauna can improve the physical, chemical and biological properties of soil, its existence is influenced by the diversity of vegetation. The research aimed to compare the diversity of soil macrofauna. The method used is a survey method. Sampling of soil macrofauna used quadrant method 50 cm x 50 cm and 100 cm x 100 cm by hand sorting in the depth of 0-20 cm. The results showed that keluwing was only found in eggplant fields, mole cricket and white grub were only found in spinach fields, large black ants were only found in the Experimental Field Station of FP UNSRI at 100 cm × 100 cm quadrant. Spiders were found in each land of the research site at 100 cm × 100 cm quadrant. The species diversity index for each quadrant of 50 cm × 50 cm had low criteria. The species diversity index of 100 cm × 100 cm quadrant had low in water spinach, eggplant, post-water spinach cropping, Experimental Field Station of FP UNSRI, with moderate criteria on spinach land. The evenness index of 50 cm × 50 cm quadrant in the fields of water spinach, spinach, eggplant and the Experimental Field Station of FP UNSRI had high criteria, and the post-water spinach cropping had medium criteria. Evenness index of 100 cm × 100 cm quadrant in spinach land with high criteria, medium criteria in water spinach, eggplant, post-water spinach cropping, Experimental Field Station of FP UNSRI.